13.5k views
5 votes
(4.18 x 10-4)(9 x 10-4)Can you please explain how to do step by step?

User Allel
by
5.6k points

1 Answer

7 votes

Answer:

3.762 x 10^-9

Step-by-step explanation:

Given the expression:


\mleft(4.18*10^(-4)\mright)\mleft(9*10^(-4)\mright)

First, we remove the brackets:


=4.18*10^(-4)*9*10^(-4)

Next, we bring the powers of 10 together.


=4.18*9*10^(-4)*10^(-4)

Next, we combine the powers of 10 by adding the exponents (since they are being multiplied).


\begin{gathered} =4.18*9*10^(-4+(-4)) \\ =37.62*10^(-8) \end{gathered}

We then obtain our final result as follows:


\begin{gathered} =3.762*10^(-1)*10^(-8) \\ =3.762*10^(-9) \end{gathered}

User Clement JACOB
by
5.1k points